The association among cervical, anal, and oral HPV infections in high-risk and low-risk women - Sehnal, Borek; Zikan, Michal; Nipcova, Monika; Dusek, Ladislav; Cibula, David; Slama, Jiri (European journal of obstetrics & gynecology and reproductive biology: X, 2019)
OBJECTIVE: The human papillomavirus (HPV) can cause premalignant and malignant tumors in the anogenital and oropharyngeal regions. The aim of this study was to describe the association in the prevalence of cervical, anal, and oral HPV infections in high-risk patients with biopsy-confirmed high-grade cervical lesion compared to low-risk women. STUDY DESIGN: A total of 718 immunocompetent women were enrolled in the study. The high-risk (HR) group consisted of 473 patients with biopsy-confirmed high-grade cervical lesion while the low-risk (LR) group consisted of other 245 women. All participants completed an anonymous self-administered questionnaire and were subjected to cervical, anal, and oral HPV genotyping using the Linear array HPV test. RESULTS: A total of 81.4% women were infected in the cervix, 43.3% in the anus, and 2.7% in the oral cavity in the HR group in comparison with only 26.9%, 24.5%, and 1.4% in the low-risk LR group, respectively. The cervical and anal HPV infections were much more frequent in the HR patients (p < 0.001); the difference in the oral HPV prevalence was not significant (p = 0.511) between groups. Concurrent cervical-anal infection was observed in 39.3% of HR women and in 8.3% of the LR patients (p < 0.001) and it significantly increased with the grade of cervical lesion (ptrend<0.001). The higher prevalence of concurrent cervical-oral, anal-oral, and cervical-anal-oral infections in HR women was statistically not significant according to the generally small oral HPV prevalence. CONCLUSIONS: All HPV infections occurred more often in HR than in LR women but not all results were statistically significant. The genotype HPV 16 was found in approximately half of all infections at all sites.
Keywords: Anal HPV infection; Human papillomavirus (HPV); Concurrent HPV infection; Oral HPV infection; Cervical HPV infection